Business Model-the Perspective of Systems Thinking and Innovation - Henten, Anders Hansen; Windekilde, Iwona (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The business model concept has gained a prominent position both in academia and among practitioners during the past 30+ years. The aim of this Special Issue of Systems is to contribute to a stronger theoretical basis for the business model concept. This includes a focus on the systemic character of business models and the systems approaches that this entails. Another important aspect is to allocate more attention to innovations of business models. The business models that emerged with e-commerce and e-business as such were in themselves innovations. However, innovations of business models have received too little attention. Most of the business models analyzed and discussed in the business model literature have been rather static instead of dynamic. This is the reason why this Special Issue of Systems, entitled 'Business Model-the Perspective of Systems Thinking and Innovation', has been developed.